Accountability and Performance Measurement: A Stakeholder Perspective - Harrison, Julie (2012)
Accountability and management accounting have strong links, especially around performance reporting. Many approaches, such as the balanced scorecard and Ramanathan’s (1985) accountability framework, stem from management accounting research and practice. Accountability and performance measurement are linked inextricably; in fact, the interpretation of performance requires accountability as its reference. Further, to make comparisons across organizations requires the identification of whose objectives are being served. The primary stakeholders provide the best accountability perspective because their goals reflect, generally, the largest section of the community. In this paper, the focus is on accountability in a school context to identify performance-reporting imperatives important to the wider public sector, including the identification of relevant stakeholders and the determination of appropriate performance models. In this way, both a framework for school performance management and a method for developing such frameworks for other applications are addressed.